Factors Affecting Machining Competency in Vocational Education: A Path Analysis Approach - Chrisna Tri Harjanto; Wagiran Wagiran; Sutopo Sutopo; Dwi Rahdiyanta; Tri Adi Prasetya (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
This study aims to analyze the direct influence of achievement motivation and workshop facilities, as well as the indirect influence through independent learning and practical machining learning on students' machining competency. A quantitative approach using path analysis, assisted by the SPSS program, was used to determine the causal relationships among variables. Before conducting the path analysis, the data met the prerequisite tests for normality, linearity, multicollinearity, and homoscedasticity, making it suitable for parametric analysis. The results show that achievement motivation and workshop facilities have a positive and significant influence on machining competency, both directly and indirectly through increasing independent learning and the effectiveness of practical machining learning. Overall, these findings confirm that both student and learning environment factors play an important role in the development of machining competency. The results of this study provide an empirical basis for the development of vocational learning strategies that are more effective and aligned with the needs of the modern manufacturing industry.